Pre-service EFL Teachers' Oral Corrective Feedback on Students' Foreign Language Production - Nurchalis, Nur Fadillah; Nur Zamzam; Ali H; Muhammad Aswad (LP2M IAIN Sultan Amai Gorontalo, 2024)
In the context of classroom communication, offering Oral Corrective Feedback (OCF) carries several advantages for enhancing students' proficiency in speaking a foreign language. It is crucial for pre-service teachers to possess the necessary skills to deliver constructive OCF to students. This research aimed to investigate the kinds of OCF provided by Pre-service EFL teachers. Two pre-service EFL teachers participated in this research. To gain data, the researchers employed recording and observation sheets to capture and document OCF within classroom settings. The data were analyzed by using descriptive analysis. The data were tabulated first. Then, each type was completed with an example of how they delivered it. After that, it was counted which type of OCF was mostly used by pre-service teachers. This research found that when providing oral comments, the two pre-service EFL teachers under observation had distinct preferences. While the other is still restricted, the first is very diversified. Nonetheless, elicitation is the OCF type that both of them employ the most frequently. This study provides benefits for different groups, the lecturer who handles teaching practicum subjects, students as foreign language learners, and pre-service EFL teachers themselves.